WTO Dispute Settlement Body Ruling on Export Ban of Indonesian Raw Nickel Ore: Private International Law Review - Imelda Martinelli; Vito Jonathan Octavo; Aristoteles G. F Siregar (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The decision of the WTO Dispute Settlement Organs regarding the ban on the export of crude nickel by Indonesia has significant implications for international trade law. This ban was opposed by the European Union because it could hamper the development of their electric-powered automotive industry which requires nickel ore as a raw material for electric vehicle batteries. Provisions in the General Agreement on Tariffs and Trade (GATT) allow export restrictions in certain situations, such as for the protection of health, safety, sanitation, or the preservation of natural resources. However, import and export bans and other non-tariff measures are not permitted. The WTO provides exceptions to quantitative restrictions that meet certain criteria. In this dispute, Indonesia was declared to have violated GATT provisions by the WTO panel. The impact of this decision is important for Indonesia, because nickel is a non-renewable natural resource and is very much needed in the country's development. Indonesia's defeat in this dispute could have a significant impact on the supply of nickel ore and its domestic use. Developed countries with high consumption already use most of the world's natural resources, while developing countries use only about 10%. WTO decisions can also affect international trade policies and relations between countries. Indonesia's defeat could reduce state revenues, discourage investment, and affect relations with the European Union. In addition, this policy may also affect the electric power automotive industry and the development of electric vehicles in the European Union. Therefore, this decision has broad and important implications in the context of international trade and bilateral relations.